Analysis of sustainable E-money usage in a developing country: Perspective from the development of the Philippines - Luq Willis A. Jimenez; Ardvin Kester S. Ong; Ma. Janice J. Gumasing; Maela Madel L. Cahigas (Acta Psychologica)
Emerging technologies and their applications are steadily gaining traction and diversifying across various domains, including the financial sector. E-money represents one such extension, facilitating cashless transactions through mobile applications which has recently bloomed in the Philippines. This research sought to offer valuable insights into the role of digital currency in developing emerging economies by integrating the UTAUT2 model with the Sustainability Theory of Planned Behavior (STPB). This study aimed to assist developing nations in gauging their communities' attitudes towards e-money from a sustainability standpoint. The study involved the analysis of responses from 638 valid participants, employing Structural Equation Modeling (SEM). The outcomes revealed that effort expectancy (β: 0.398) significantly influenced e-money adoption, as per the integrated UTAUT2 and STPB framework, followed by other UTAUT2 domains. Subsequently, attitude (β: 0.368) and subjective norm (β: 0.273) followed in terms of their impact, alongside perceived behavioral control (β: 0.26) and the sustainability domains. These findings shed light on users' perception of e-money as a valuable addition to their daily lives, primarily due to its transactional convenience. Users also believe that e-money enhances their ability to achieve personal goals, giving them control over their time and convenience. As a result, these study findings are pertinent for comprehending user intentions, especially within the context of the continuous advancement of technology.